Multiplex optical urinalysis for early detection of drug-induced kidney injury - Cheng, Penghui (2021)
Drug-induced kidney injury (DIKI) is a significant contributor of both acute and chronic kidney injury and remains a major concern in drug development and clinical care. However, current clinical diagnostic methods often fail to accurately and timely detect nephrotoxicity. This study reports the development of activatable molecular urinary reporters (MURs) that are able to specifically detect urinary biomarkers including γ-glutamyl transferase (GGT), alanine aminopeptidase (AAP), and N-acetyl-β-d-glucosaminidase (NAG). By virtue of their discrete absorption and emission properties, the mixture of MURs can serve as a cocktail sensor for multiplex optical urinalysis in the mouse models of drug-induced acute kidney injury (AKI) and chronic kidney disease (CKD). The MURs cocktail not only detects nephrotoxicity earlier than the tested clinical diagnostic methods in drug-induced AKI and CKD mice models, but also possesses a higher diagnostic accuracy. Therefore, MURs hold great promise for detection of kidney function in both preclinical drug screening and clinical settings.